PO073 Peduncular hallucinations after stn-dbs: lesion or a coincidence?. (1st December 2017) - Lowry, Lindsey; Fletcher, Nick; Hammersley, Beth; Panicker, Jay; Foy, Kevin; Byrne, Patricia; Eldridge, Paul; Alusi, Sundus
Abstract : Peduncular hallucinations are known to be associated with midbrain, pontine and thalamic lesions. They can be spontaneous or in response to visual stimuli. However, 'complex' distortion of perception has only been reported in association with dorsomedial thalamic lesions. Delirium, psychosis and visual hallucinations have been reported after Deep brain stimulation (DBS) of the subthalamus nucleus (STN). However, ' fantastically' distorted Peduncular hallucinations have not. We report the case of a 47 year old female with young onset Parkinson's disease and intact preoperative cognition, who experienced complex visual hallucinations within a week of STN stimulation with no motor/sensory deficit. She was alert and oriented but described, in detail, seeing small animals and clown faces in reflective surfaces as well as creepy polar bears that sat on her legs and made them feel cold. Switching the stimulation off, altering contact sites and reducing dopaminergic drugs had little impact. The stimulation was restarted; Quetiapine was given and she improved after 8 weeks of hospitalisation. It is possible that peduncular hallucinations in our patient resulted from a peroperative dorsomedial thalamus micro-lesion. Given the intensity and distress of this type of hallucinations, prompt recognition and treatment with atypical antipsychotics should be considered.